1982
DOI: 10.3133/ofr82868
|View full text |Cite
|
Sign up to set email alerts
|

Geohydrologic data from sandstone aquifers in southwestern Kansas

Abstract: Boundary of I ° ° o o 8,00 0^X2> study area-l North Q ^ ^ TOT 0 eft* Chloride (Cl) 250 Fluoride (F) ' 1.5 Nitrate (NOs) 45 Water levels in wells that typify the seasonal fluctuations and longterm trends in some places in the sandstone aquifers are available in table 6 and several published reports. For Hodgeman and northern Ford Counties, water levels in wells in the Dakota Formation are given by Lobmeyer and Weakly (1979). Water-level records during 1966-70 are available from Broeker

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Additional study of the effect on the quantity and quality of water flowing into and out of the High Plains aquifer would be of value at locations where it is presently occurring and at locations where interchange might be induced further. Previous studies have dealt with parts of the issue to a large degree (U.S. Geological Survey, 1966;Lobmeyer and Weakly, 1979;Kume and Spinazola, 1982;Spinazola and Dealy, 1983;Kume, 1984;Watts, 1989), but in light of information developed in the present study, further investigations would be of value.…”
Section: Water Supply and Water-storage Potential Great Plains Aquifementioning
confidence: 78%
“…Additional study of the effect on the quantity and quality of water flowing into and out of the High Plains aquifer would be of value at locations where it is presently occurring and at locations where interchange might be induced further. Previous studies have dealt with parts of the issue to a large degree (U.S. Geological Survey, 1966;Lobmeyer and Weakly, 1979;Kume and Spinazola, 1982;Spinazola and Dealy, 1983;Kume, 1984;Watts, 1989), but in light of information developed in the present study, further investigations would be of value.…”
Section: Water Supply and Water-storage Potential Great Plains Aquifementioning
confidence: 78%
“…Macfarlane (1993) later extended this name to include sandstone aquifers in stratigraphically equivalent rock units in southeastern Colorado. Kume and Spinazola (1985) showed that hydraulic heads in the sandstone aquifers of the Dakota Formation are similar to hydraulic heads in the Cheyenne Sandstone over much of southwestern Kansas. This suggests that even though the sandstone aquifers are separated by a regional confining unit, they act together as a single hydraulic unit.…”
Section: Dakota Aquifer Systemmentioning
confidence: 94%
“…Reports by Keene and Bayne (1977), Lobmeyer and Weakly (1979), Kume and Spinazola (1982;, and Kume (1984) described the ground-water resources of the Lower Cretaceous and Jurassic rocks in western Kansas. Hydrogeologic information about the sandstone aquifers in adjacent states was given by McLaughlin (1954) for Baca County, Colo., by Voegeli and Hershey (1965) for Prowers County, Colo., and by Hart and others (1976) for the Oklahoma Panhandle.…”
Section: Methods Of Investigation Previous Investigationsmentioning
confidence: 99%